Negotiating Sharia and Sustainability: An Empirical Study of Dynamic Margin Strategies in Indonesian BMTs - Mansur Mansur; Moh. Khoirul Umam; Fathiyatun Nikmah; Fitria Nur Masithoh (Institut Agama Islam YPBWI Surabaya, 2026)
This study analyzes how Indonesian BMTs balance Sharia compliance and financial viability through dynamic margin strategies in Murabaha financing. Using a qualitative case study of BMT Al-Iktisab, Aeng Nyonok Branch, East Java, data were collected via in-depth interviews with the branch manager, financing officers, and selected members, supported by observation and internal document review. Thematic analysis revealed that margin determination is negotiated rather than fixed: a base pricing formula is applied but adjusted through term-shortening discounts and loyalty-based rebates, framed as flexible ribḥ within a transparent cost-plus structure. This adaptability strengthens competitiveness and customer loyalty while maintaining institutional sustainability, illustrating a practical negotiation between commercial pragmatism and religious principles. The study contributes to Islamic microfinance scholarship by providing empirical evidence of how Sharia compliance is operationalized in resource-limited community contexts. It advances the concept of “negotiated sustainability” to explain the hybrid logic guiding BMT practices and their innovation in adapting classical Islamic finance contracts to local socioeconomic realities.